Rejeito de manganês, proveniente da Amazônia Oriental, em substituição parcial do agregado miúdo natural em concreto - SILVA JÚNIOR, Paulo Rogério (Universidade Federal do Pará, 2019)
Research on partial or total substitution of the natural fine aggregate for ore tailings has gained strength in recent years. Most part of these tailings are destined to dams, which are subject of ruptures resulting in social, economic and environmental loses. The most recent example is the rupture of Brumadinho-MG dam in january, 2019. Despite of all the risks associated to the mining activity, the extraction of ore tends to increase due to the final products generated by this activity such as steel, batteries and electronics. Natural sand is mostly obtained by dredging activity, which involves the deforestation of certain areas and the possible contamination of the water with diesel oil from dredgers. This research aims to study the partial replacement of natural sand by manganese tailing (in 15%, 20%, 25% and 30% proportions) from the eastern Amazonia, Marabá-PA municipality, for the construction of structural concrete without the use of superplasticizer. Analyzed the results for the test of workability, mechanical strength, water absorption and microstructure for the samples of concrete with and without tailings. It has been found that manganese tailing is a thin material that has a high specific surface, which demands high demand for water when compared to the reference concrete. It was verified that there was a decrease in the mechanical properties of the refuse concrete due to the added water, however, the water absorption was equal to the reference one.